2019
DOI: 10.3390/systems7030033
|View full text |Cite
|
Sign up to set email alerts
|

Review of Kalman Filter Employment in the NAIRU Estimation

Abstract: The aim of the paper is to provide a recent overview of Kalman filter employment in the non-accelerating inflation rate of unemployment (NAIRU) estimation. The NAIRU plays a key part in an economic system. A certain unemployment rate which is consistent with a stable rate of inflation is one of the conditions for economic system stability. Since the NAIRU cannot be directly observed and measured, it is one of the most fitting problems for the Kalman filter application. The search for original, NAIRU focused an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In a state-space model, Kalman filter is also an algorithm for generating a minimum mean square error forecast. The filter is a recursive algorithm for linearly updating the onestep-ahead estimate of the state mean and variance, given new information (that is, measurement knowledge of the system model and statistical descriptions of its inaccuracies, noise, and errors), (Ole, 2015, Fronckova, Prazak, & Soukal (2019.…”
Section: 332b) Kalman Filtermentioning
confidence: 99%
“…In a state-space model, Kalman filter is also an algorithm for generating a minimum mean square error forecast. The filter is a recursive algorithm for linearly updating the onestep-ahead estimate of the state mean and variance, given new information (that is, measurement knowledge of the system model and statistical descriptions of its inaccuracies, noise, and errors), (Ole, 2015, Fronckova, Prazak, & Soukal (2019.…”
Section: 332b) Kalman Filtermentioning
confidence: 99%
“…In a state-space model, it is also an algorithm for obtaining a minimum mean square error forecast. The "Kalman filter" is a recursive algorithm for linearly updating the one-step-ahead forecast of the state mean and variance, given new information (that is, measurement knowledge of the system model and statistical descriptions of its inaccuracies, noise, and errors), (Ole, 2015, Fronckova, Prazak, & Soukal (2019.…”
Section: 332b) Kalman Filtermentioning
confidence: 99%
“…By using this filter, the logarithmic likelihood function of the state-space model can be estimated and, thus, parameters of the model areAlichi et al (2017) shows that the use of additional exogenous variables contributes to reducing the sensitivity of the model. For a systematic review of the literature related to the summary results of the studies carried out on this subject,Richardson et al (2019) andFronckova et al (2019) can be suggested.Recent studies on the structural unemployment and Beveridge curve in the Turkish economy is limited. Us (2014) estimates NAIRU and a time-varying Phillips curve for the Turkish economy by system approach for 2000Q1-2013Q3.…”
mentioning
confidence: 99%